(untitled) (The Journal of Psychology and Sociology, 2014)
This article is devoted to a problem of formation of valuable orientations of the humanistic personality in the conditions of information violence and distribution of new types of an addiction in the youth environment. Article purpose: to offer the optimal, considering a condition of modern society social and pedagogical conditions allowing to reduce sharpness of a problem, relying on the given domestic and foreign experts and own empirical researches. Research problems included search on the basis of system and culturological approaches of possible ways of formation of humanistic type of the identity of the modern school student. In the conditions of negative impact of mass media on public consciousness, blurring of the valuable bases of social culture, such process becomes rather problematic. It was important to us to reveal the ways of creating favorable conditions of socialization of school students accepted in the conditions of information war for minds of youth; to define ways of blocking and prevention of a computer addiction as the most dangerous to the developing personality in social sense substituting the real world for the virtual. In article problems of formation of the complete personality, the dominating social values attractive to modern school students of the senior classes are described; the comparative analysis of social and valuable orientations of school students and students is given; similarity and a certain divergence in valuable preferences and tastes of modern school students and students is revealed, the actual forms and methods of social and pedagogical support and formation of humanistic potential of the personality, algorithm of the organization of teaching and educational process and priorities facing modern school establishments are defined.